World Economic Outlook, October 1991. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1991)
This paper highlights that the growth of world economic activity in 1991 is expected to fall to a scant 1 percent, the lowest in any year since 1982, when the industrial economies were in recession. The slowdown in the expansion of world trade would be considerably more pronounced. Output growth in the industrial countries as a group is expected to average 1u percent in 1991, reflecting a fall in economic activity in a number of countries. Cyclical divergences among the major countries persisted in the first half of 1991.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet